IMPLEMENTATION OF LOCAL GOVERNMENT RESPONSIBILITY FOR DAMAGED ROADS - Zulkarnaini; Irawan Harahap; Miftahul Haq (JILPR Journal Indonesia Law and Policy Review, 2026)
The purpose of this study is to analyze the implementation of local government responsibility for damaged roads in Tapung Hulu District, Kampar Regency, to analyze the obstacles in the implementation of local government responsibility for damaged roads in Tapung Hulu District, Kampar Regency, and to analyze efforts to overcome obstacles in the implementation of local government responsibility for damaged roads in Tapung Hulu District, Kampar Regency. The method used is sociological legal research. Based on the results of the study, it is known that the implementation of local government responsibility for damaged roads in Tapung Hulu District, Kampar Regency has not been running optimally because there are still road sections that have been damaged for a relatively long time, thus affecting the safety of road users, the smooth mobility of the community, and economic activities. This condition indicates that the implementation of local government obligations has not fully met the principles of implementing safe, secure, sustainable roads and providing quality public services as mandated by laws and regulations. The obstacles are: First, limited regional financial capacity causes the budget for road maintenance and improvement to not be able to meet all the needs for road infrastructure development. Second, the weak road monitoring and maintenance system causes minor damage not to be immediately addressed so that it develops into severe damage that requires greater rehabilitation costs. Third, the less than optimal implementation of criminal liability against road operators who neglect to carry out their obligations as stipulated in Article 24 and Article 273 of Law Number 22 of 2009 concerning Road Traffic and Transportation, so that the preventive function of criminal law has not provided a deterrent effect in increasing compliance of road operators with their legal obligations. Efforts to overcome these obstacles include optimizing budget management through the preparation of development priorities based on the level of road damage and community needs, as well as utilizing other legitimate funding sources in accordance with statutory provisions. Furthermore, local governments need to strengthen the system of supervision, inventory, and periodic road maintenance by utilizing information technology and improving inter-agency coordination so that road damage can be detected and handled more quickly. In addition, it is necessary to optimize law enforcement against road operators who neglect to carry out their obligations through the application of criminal provisions in accordance with statutory regulations, accompanied by increased internal supervision and accountability of government officials, so as to create legal certainty, protection for road users, and improve the quality of public services in the field of road infrastructure.